الجماعة الصوفية كوعي وممارسة - شتوح, أحمد عبد اللطيف; دبلة, عبد العالي (Sciences de l'Homme et de la Société; No 25 (2017): مجلة علوم الإنسان والمجتمع, 2017)
إن البحث في أصول و ممارسات الطرق الصوفية يفضي بنا إلى الوقوف على جملة من الروافد المعررفية والاارخية الأساسية، التي تضافرت لافرز شكلا من أشكال الوعي الجمعري داخل المجامعرات الإسلامية، وهو ما يفسّر الكثير من أوضاع هذه الظاهرة على حسب البيئة التي احاضناها، ومن ثم كيفية تفعرليها. وعليه سنحاول في هذه الدراسة أن نبحث في الشروط الاارخية و السوسيولوجية التي أسست لهذا النوع من الادين، و نحاول الحفر في الشروط البنيوية التي تجعرل من الطريقة الصوفية حقلا تربويا اجاماعيا قائم بذاته في المجامع العرربي الإسلامي. Abstract: The search in the oigins and practicies of sufi (sophism) orders requires us to stand on a number of trubitaries and cognitive historical bases , wihich combined and make a kind of collective consciousness in the bottom of islamic communities, that explain the main of this phenomenon .Accroding its enverenement and there how it can be activated. And by this study we will try to look at the historical conditions and sociological which founded for this type of religivisity, and we triyed to drill in to the structural conditions which make sufi(sophism) socialy educationally , stand alone. In the arab_ muslims (islamic) community.